2011
DOI: 10.1186/1687-5281-2011-2
|View full text |Cite
|
Sign up to set email alerts
|

Invariant representation for spectral reflectance images and its application

Abstract: Spectral images as well as color images observed from object surfaces are much influenced by various illumination conditions such as shading and specular highlight. Several invariant representations were proposed for these conditions using the standard dichromatic reflection model of dielectric materials. However, these representations are inadequate for other materials like metal. This article proposes an invariant representation that is derived from the standard dichromatic reflection model for dielectric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…3 Ibrahim et al tried to solve the specular problem for metal materials. 4 Ashton et al proposed a shadow removal method in hyperspectral images. 5 Most HSI-based target detection methods use spectral preprocessing to reduce the illumination effects.…”
Section: Introductionmentioning
confidence: 99%
“…3 Ibrahim et al tried to solve the specular problem for metal materials. 4 Ashton et al proposed a shadow removal method in hyperspectral images. 5 Most HSI-based target detection methods use spectral preprocessing to reduce the illumination effects.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we proposed an invariant representation for a variety of real-world objects including metals and dielectrics [8]. We showed that the normalized surface spectral reflectance by the minimum reflectance was invariant to illumination effects and the representation was effective to spectral imaging applications [9]. However, the method requires an expensive and special measurement device such as a spectral imaging system and a standard white reference.…”
Section: Introductionmentioning
confidence: 99%